Peran Buruh Pabrik Perempuan dalam Meningkatkan Pendapatan Keluarga Perspektif Ekonomi Islam (Studi Kasus Desa Gemiring Kidul Kecamatan Nalumsari) - Kusrini, Eni; Suryani, Ika Putri (Universitas Islam Negeri Sunan Kudus, 2022)
The development of industrialization is marked by the establishment of labor-intensive factories in Jepara Regency which has an impact on the opening of job opportunities which are dominated by women which will have an impact on increasing the income and welfare of the surrounding community. With these factories, many women in Gemiring Kidul Village work as factory workers to meet the needs of their families. the involvement of women in earning a living creates a dual role in the household.This study aims to determine the role of women who work as factory workers in increasing family income from an Islamic economic perspective as well as the impact and solutions of women who work as factory workers in Gemiring Kidul Village. This research was conducted in Gemiring Kidul Village with 16 female factory workers as the subject. This research uses qualitative research methods with the type of field research (field research). data obtained through interviews, observation, and documentation. data analysis using data reduction, data presentation, and verification.This study concludes that the role of women workers in Gemiring Kidul Village is quite large in an effort to increase family income, especially in meeting consumption needs, household equipment, children's education costs and other household needs. The positive impact of housewives in Gemiring Kidul Village who work as factory workers is that they get income that can be used to meet household needs, improve the household economy, and be able to finance children's education costs. While the impact is limited time to gather with children and husband. The solution for women who work as factory workers in overcoming family problems is by establishing good communication and creating a harmonious family with family members, namely by making the best use of time during work holidays and maintaining quality time with spouse and children, working together well in dealing with household problems, as well as entrusting child care to the right people, namely with their families and grandmothers. In an Islamic perspective, the work of housewives as factory workers is in accordance with the provisions of Islamic sharia, namely with the permission of the husband and brings benefit to the family.